Enhancing Sustainability in Transportation Education: A Multimodal Curriculum Approach - Simanjuntak, Marudut Bernadtua; Barasa, Larsen; Alamsyah, Jaya; Wulandari, Retno Sawitri (Politeknik Ilmu Pelayaran Semarang, 2024)
This research critically examines the integration of sustainability principles into transportation education, focusing on multimodal curriculum development. Qualitative research methods are employed to investigate the perspectives of 39 cadets studying multimodal transportation, logistics, transportation safety, and law and road management at a transportation institution. The findings reveal varying levels of awareness and integration of sustainability in education, with participants highlighting the need for a more comprehensive and practical curriculum. Participants also emphasize the importance of industry collaboration, research, and policy advocacy in enhancing sustainability focus. The research underscores the urgency of preparing future professionals for the globalized, environmentally conscious transportation industry. By incorporating participants' suggestions, educational institutions can enhance sustainability education and contribute to a more sustainable and resilient transportation sector.